Strategi Digital Public Relations Pegiat Podcast dalam Membangun Brand Engagement (Studi Kasus dalam Podcast Duo Budjang) - Bella Chitra; Roswita Oktavianti (Prologia, 2019)
This research studies about the digital public relations strategy of podcast enthusiasts in developing their brand engagement. The researcher used concepts of digital public relations and brand engagement in explaining the analysis. The scope of digital public relations concepts cover online or website publicity, social media, and online communities. Meanwhile, the concept of brand engagement can be seen in active interactions with followers or listeners. This research is a qualitative research using the case study methodology. The case studies used the Duo Budjang podcast. This study finds that the promotion on social media is more effective and efficient than on websites, especially on Instagram because the majority of the users are millennials. The promotion will be successful if the selection of media channels is tailored according to the target audience and consistent in its management. In developing the engagement, podcast enthusiasts pay attention to and make active interactions on both online and offline. One success story of the engagement is the existence an online or virtual community established by the loyal listeners of the podcasts. The community also helps in promoting the podcasts. Penelitian ini mengangkat tentang strategi digital public relations pegiat podcast dalam membangun brand engagement. Konsep yang digunakan yaitu digital public relations dan brand engagement. Konsep digital public relations seperti publisitas online atau website, media sosial, dan komunitas online. Sedangkan konsep brand engagement dapat dilihat pada interaksi yang aktif terhadap followers atau pendengarnya. Penelitian ini merupakan penelitian kualitatif menggunakan metode studi kasus. Studi kasus dilakukan terhadap podcast Duo Budjang. Hasil penelitian ini adalah promosi di media sosial lebih efektif dan efisien daripada di website, khususnya di Instagram karena mayoritas pengguna adalah generasi milenial. Promosi akan berhasil jika pemilihan saluran media sesuai target audience dan konsisten dalam pengelolaannya. Dalam membangun engagement, pegiat podcast memperhatikan dan membuat interaksi yang aktif baik di dalam jaringan (daring) maupun di luar jaringan (luring). Salah satu contoh keberhasilan dari engagement yang dibangun adalah adanya komunitas online atau virtual yang merupakan pendengar setia podcast. Komunitas juga membantu dalam mempromosikan podcast.